PENGARUH PAJAK PENGHASILAN BADAN, KEPEMILIKAN ASING, DAN UKURAN PERUSAHAAN TERHADAP TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2022 - Laia, Imelda Venika; Sembiring, Yan Christin Br (Jurnal Ilmiah Akuntansi (JIMAT), 2025)
This study aims to examine the effect of corporate income tax, foreign ownership, and company size on transfer pricing partially and simultaneously. The population in this study, manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2019-2022 with a population of 88 companies. The number of samples was 11 companies in 4 years of the study period with 44, outlier data as many as 12 so that the study had 32 observations. Sampling using purposive sampling technique. The analysis method used is descriptive statistical test, classical assumption test which includes normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. Using multiple linear regression analysis, hypothesis testing, and determination testing using SPSS version 25 to process data. The results of this research show that corporate Income Tax partially has a positive and significant effect on transfer pricing, foreign ownership has no effect on transfer pricing and company size has no effect on transfer pricing, while simultaneously corporate Income Tax, foreign ownership, and company size has a positive and significant effect on transfer pricing in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period.